Antimicrobial effect of Rhus coriaria L. (sumac) total extract on skin isolates Staphylococcus epidermidis and Corynebacterium xerosis - MR Fazeli; H Ashtiani; MM Ahmadian attari; H Jamalifar; A Zaheri (Institue of Medicinal Plants, ACECR, 2006)
Background: Sumac (Rhus coriaria L. epicarp) is an Iranian traditional spice which is widely used in the country. Following the recent efforts to look for healthy herbal remedies with antimicrobial potential, the effect of total extract of sumac was investigated on some clinical isolates of skin bacteria. Methods: Hydroalcholic extract of Sumac prepared from Tehran botanicals drug market was extracted by maceration method using 80% ethanol. The antimicrobial activity of the extract was studied and compared with the commercial antibiotic of Gentamycin as positive control. Minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) of the extract were determined against the skin bacteria of Corynebacterium xerosis and Staphylococcus epidermidis. The skin bacteria used included ten axilla isolates of C. xerosis, seven skin isolates of S. epidermidis and also a standard strain of S. epidermidis ATCC 12229. Results: The results obtained in this study indicate considerable antimicrobial effect of Sumac on skin bacteria. Sumac showed bactericidal effect on all of the tested strains. The MIC obtained against most of the microorganisms was 1.56 mg/ml. Discussion: The antimicrobial effect of Sumac on skin bacteria looks promising. Further studies should be conducted on identification and purification of the potential antimicrobial compound of Sumac which could be used in the antiseptic products.